Self-Medication Behavior: Self-Medication Behavior - Brigitta Olivia Sinulingga (Journal of Midwifery and Nursing, 2020)
In developing countries self-medication behavior is something that is very often found. This happens because self-medication behavior provides a cheaper and easier alternative for the community. Coupled with the ease in purchasing drugs. Self-medication is usually done to overcome complaints and minor illnesses that are often experienced by the community, such as fever, pain, dizziness, cough, influenza, stomach ulcers, intestinal worms, diarrhea, skin diseases and others. Self-medication behavior patterns have a higher prevalence in developing countries compared to developed countries. Based on the 2011 Susenas results, BPS noted that there were 66.82% of sick people in Indonesia who did self-medication. This phenomenon is very common in young people, especially students, and continues to increase along with media exposure and increased drug advertising. This poses a greater threat to the young population. To do self-medication correctly, people need to have clear and reliable information about the drugs they used. If self-medication is not done properly, there is the risk of another side effect due to improper drug use.